Ethnic identity, leadership style on teacher efficacy, and student learning outcomes at the Huaulu ındigenous ınland school, North Seram Island - Utari, Tria Ina (Jurnal Sosiologi Dialektika, 2023)
Personality and habits that exist in the group will shape ethnic identity, especially in shaping experiences and leadership roles in the group. Ethnic identity was used to investigate how behavior correlates in terms of leadership style and teacher efficacy when in organizations (schools). This study aims to determine the various influences that appear in all research variables. This study uses the Smart PLS 3 program. The data collection technique uses a questionnaire. Based on the findings of the ethnic identity variable at the Huaulu Interior Elementary School, it shows that only the relationship between ethnic identity and teacher efficacy has a positive and significant effect of 0.755. Ethnic identity has no significant effect on leadership style 0.669. Ethnic identity has no significant effect on student learning outcomes, which is 0.943. Leadership style has no significant effect on student learning outcomes, namely 0.83. Teacher efficacy has no significant effect on student learning outcomes, namely 0.560. This study concludes that ethnic identity has the most significant effect on improving teacher self-efficacy. In the future, this study can become a reference for the development of effective cross-ethnic leadership by adding diversity to develop leader-follower relationships.